The Effect of Universal Design of Campus Facilities for Person with Disabilities (Case Study: Universitas Mercu Buana, Jakarta and University of Daegu, South Korea) - Harahap, Rachmita Maun; Santosa, Imam; Martokusumo, Widjaja (Universitas Mercu Buana, 2019)
Interiority is not just the science of interior design that meets the needs of function and aesthetics alone. Both of these are indeed the main 'task' in interior design. Each building is design and built to fulfill certain functions. Hotels, apartments, and houses for example, serves as a means of accommodation. Restaurant serves as a commercial building that meets the needs of food. A public building should be accessible and used by a variety of different needs. These buildings must be accessible to those who can see or not (blinds), walkers and wheelchair users, and those who are able to listen or not (deaf/hard of hearing). This paper is study of application of universal design that is accessible of campus buildings that function as container of Tri Dharma of Higher Education activity. The case studies taken in this research are Universitas Mercu Buana in West Jakarta and University of Daegu in South Korea. The study was conducted by studying the universal design of the two universities by considering two parameters, namely universal design and usability, by conducting literature studies and user interviews. From the results of the study it is found that universities in Daegu have made universal design and usability factors an important part of design, while Universitas Mercu Buana in West Jakarta hasn’t yet fully made these two factors as part of the design, with many facilities not being able to accessed and used universally well.